The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/inorganics5040081
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties and Reversible Hydrogenation of LiBH4–Mg2FeH6 Composite Materials

Abstract: Abstract:In previous studies, complex hydrides LiBH 4 and Mg 2 FeH 6 have been reported to undergo simultaneous dehydrogenation when ball-milled as composite materials (1 − x)LiBH 4 + xMg 2 FeH 6 . The simultaneous hydrogen release led to a decrease of the dehydrogenation temperature by as much as 150 K when compared to that of LiBH 4 . It also led to the modified dehydrogenation properties of Mg 2 FeH 6 . The simultaneous dehydrogenation behavior between stoichiometric ratios of LiBH 4 and Mg 2 FeH 6 is not y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Chaudhary, Dornheim, Orimo and co-workers investigated a transition metal containing a reactive hydride composite (1 − x)LiBH 4 -xMg 2 FeH 6 , and measured excellent pressure-composition-isothermal (PCT) data [21]. The results indicate that the same stoichiometric reaction (x = 0.5) occurred in all investigated samples with optimal hydrogen storage and reversibility properties.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Chaudhary, Dornheim, Orimo and co-workers investigated a transition metal containing a reactive hydride composite (1 − x)LiBH 4 -xMg 2 FeH 6 , and measured excellent pressure-composition-isothermal (PCT) data [21]. The results indicate that the same stoichiometric reaction (x = 0.5) occurred in all investigated samples with optimal hydrogen storage and reversibility properties.…”
mentioning
confidence: 89%
“…Moreover, the x = 0.5 composite could be reversibly hydrogenated for more than four cycles without degradation of the H 2 capacity. The authors conclude that magnesium hydride plays a vital role as an intermediate in the hydrogen release and uptake reactions [21].…”
mentioning
confidence: 98%
“…To date, the reported reaction mechanism of joint 2LiBH 4 -Mg 2 FeH 6 decomposition has been investigated under isothermal conditions, and the results have been reported by several groups [11,12,[14][15][16][17][18], while the knowledge of the actual reaction path for decomposition under dynamic heating of the mixture, and the present competition between different possible decomposition reactions, is limited. Indeed, the current study's goal lies in investigating the dehydrogenation of the 2LiBH 4 -Mg 2 FeH 6 assemblage mechanism in detail, following the applied reaction conditions such as dehydrogenation under vacuum, reaction with temperature-programmed dehydrogenation (dynamic decomposition), and isothermal dehydrogenation using in situ X-ray diffraction data.…”
Section: Namementioning
confidence: 99%
“…In a study by Li et Al. on a composite of Mg 2 FeH 6 and LiBH 4 in different compositions (Mg 2 FeH 6 /LiBH 4 molar ratios (X) of 0.25, 0.5, and 0.75), the authors reported X = 0.5 as the correct stoichiometric ratio for Mg 2 FeH 6 and LiBH 4 joint decomposition [18].…”
Section: Introductionmentioning
confidence: 99%